Pengaruh Suasana Cafe dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan pada Soehendar Coffee Kota Bima - Fahad Pramadani Putra; Ita Purnama; Sri Ernawati (Indo Publishing, 2025)
This study aims to determine the effect of cafe atmosphere and service quality on customer satisfaction at Soehendar Coffee, as measured by partial (t-test) and simultaneous (F-test) tests. The population in this study was all consumers who have purchased from Soehendar Coffee. The sampling technique used a purposive sampling method with a sample size of 96 people. The results of the study indicate that: 1). Cafe atmosphere does not significantly influence customer satisfaction at Soehendar Coffee in Bima City. 2). Service quality significantly influences customer satisfaction at Soehendar Coffee in Bima City. 3). Cafe atmosphere and service quality significantly influence customer satisfaction at Soehendar Coffee in Bima City.